Co-production of ferulic acid and p-coumaric acid from distiller grain by a putative feruloyl esterase discovered in metagenome assembled genomes - Zhang, Jiaqi; Tang, Hongzhi; Yu, Xun; Xue, Dongsheng; Li, Mei; Xing, Xingyue; Chen, Hao; Chen, Jia; Wang, Chongju; Gong, Chunjie (Journal of cleaner production, 2024)
The brewing industry generates a large amount of distillation waste, causing environmental pollution and resource wastage. In this study, a putative gene encoding feruloyl esterase detected in 33 bins using metagenomic sequencing, was expressed to exogenously to generate a recombinase with a molecular weight of 40.8 KDa. The feruloyl esterase has been optimized through codon optimization and signal peptide truncation to exhibit optimal activity at pH 6.0 and 50 °C, specifically when using 4-nitrophenyl trans-ferulate as its substrate. By employing this enzyme, p-coumaric acid and ferulic acid were simultaneously produced using brewing waste of distilled spent grain with husk. The yield of the two phenolic acids amounted to 91.2 μg and 89.25 μg from 1 g of distilled spent grain with husk, respectively. Although the yield obtained was lower than that from wheat bran and corn cob, the strategy serves as a model for the high-value utilization of brewing waste and has hold application potential. The integration of enzyme catalysis and metagenomic sequencing revealed a significant importance for clean production from agricultural processing industrial waste. The strategy for ferulic acid and p-coumaric acid production from distilled spent grain with husk by catalysis of a feruloyl esterase from Metagenomic sequencing of forest soils. Natural biomass containing hemicellulose could be degraded by the feruloyl esterase to produce high-value chemicals. It provided a gentle and environmentally friendly method for the biomass utilization. [Display omitted] •An encoding gene for feruloyl esterase was obtained through metagenomic sequencing.•The enzyme catalyzed the co-production of p-coumaric acid and ferulic acid.•A method for recovering chemicals from distilled spent grain with husk is provided.•The yield of p-coumaric acid and ferulic acid amounted to 91.2 μg/g and 89.25 μg/g.